Perancangan Aplikasi Augmented Reality Sebagai Media Pengenalan Struktur Lapisan Matahari Berbasis Android - Indra Wijaya; Mufida Khairani (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
The structure of the Sun’s layers is a complex subject as it involves multiple physical phenomena, making it difficult to understand when explained only through conventional media such as text or static images. This research aims to design and develop an Android-based Augmented Reality (AR) application as a medium for introducing the structure of the Sun’s layers. The method used is the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, testing, and distribution. The application was built using marker-based AR technology that presents interactive 3D models of the Sun’s layers, accompanied by descriptions and audio explanations to strengthen user understanding. The implementation results show that the application runs smoothly on Android devices, providing key features such as an AR camera and interactive quizzes. Black-box testing confirmed that all functions work as intended, while respondent testing indicated that the application is easy to use, displays 3D objects clearly, and increases students’ learning interest. Therefore, this application is proven to be effective as an innovative learning medium, simplifying the visualization of the Sun’s structure, and enhancing interactivity and engagement in the learning process.